PEGEMBANGKAN KOMPETENSI PEDAGOGIK GURU MELALUI SUPERVISI AKADEMIK PENGAWAS DI SEKOLAH BINAAN : PENGAWAS SATUAN PENDIDIKAN KECAMATAN BINAKAL - ENY RAHAYU (Mitra Pendidikan, 2021)
The aims of this research are 1). to find out the stages of implementing academic supervision in improving the pedagogic competence of teachers 2). To find out the success of academic supervision of supervisors in developing teacher pedagogic competencies. 3). To find out the obstacles in the implementation of academic supervision of supervisors in developing teacher pedagogic competencies. By looking at the formulation of the problem, this research is a type of qualitative research based on field research with a naturalistic descriptive approach, which is an approach in research that describes the condition of the object and research subject with a reasonable picture or what it is (Suharsimi Arikunto. 2001). Because this research is qualitative with a naturalistic descriptive approach, the research is carried out in natural conditions (natural setting). Sources of data are natural situations, researchers collect data based on observations of fair situations, as they are, and researchers are the key instrument that conducts observations and interviews themselves (Sugiyono, 2013). The object of this research is the teacher of SD Negeri 1 Jeruk Soksok 1 as the target school which is located at Jalan Jeruk Soksok, Binakal District, Bondowoso Regency, Postal Code 68251. This research was carried out for 3 months, from September to November 2019 The type of data, because this research is a field research (Field Research), namely research conducted in the field or the field of occurrence of symptoms (Sutrisno.2000). So the type of data needed and used is the type of field data presented descriptively. While the data sources needed are primary data sources and secondary data sources obtained through observation, interviews and documentation. The data analysis in this study followed the model of Miles and Huberman (Sugiyono. 2002). The steps of data analysis in this study are as follows (H. M. Arifin.2003) 1). Examine the data that has been collected from the results of observations, interviews and documentation. 2). Carry out data reduction by taking data that can be processed further. 3). Arrange data in relevant units. 4). Doing categorization while coding (coding) e. Conducting data validity checks f) Interpreting data and drawing conclusions inductively by way of thinking based on specific facts, then directed to drawing general conclusions Based on the description in the data that has been discussed in chapters three and four, the authors can conclude the results of the research that the authors did as follows: 1). The implementation stage was carried out well which included three stages of pre-observation (initial meeting), observation (observation of the learning process), and post-observation (evaluation and giving feedback) 2). The implementation stage of supervision can be said to be successful with indicators that most teachers can make learning administration properly and correctly, besides that teachers in the teaching and learning process are able to utilize media, facilities and technology available in schools and the surrounding environment 3). Implementation barriers. Obstacles to the implementation of supervisory academic supervision can be categorized into two aspects, namely structure and culture.